Assessment could demonstrate learning gains, but what is required for it to do so?. Issue 1 (1st January 2018) - Boud, David
Abstract: A ready source of data to investigate learning gain is that generated normally through student assessment. That such data cannot currently be used for this purpose needs explanation and the refreshment of assessment thinking to bring it in line with thinking about standards. This opinion piece discusses what is required for this to occur.